PENGARUH BRAND AWARENESS, BRAND IMAGE, DAN BRAND LOYALTY, TERHADAP PARENT BRAND â€œTOP COFFEEâ€ DI SURABAYA DENGAN BRAND EXTENSTION SEBAGAI VARIABEL INTERVENING - SANTOSO, DAVID (Universitas Katolik Widya Mandala Surabaya, 2013)
The expansion of the brand (brand extension) is a situation where a company to use an existing brand to launch a product in a new category. Several things can affect the expansion of the brand is brand awareness, brand image, and brand loyalty. The research aims to know the influence of brand awareness, brand image, and brand loyalty, to the parent brand